Do Store Image and Customer Values Influence Purchase Intention of Private Label Products among Generation Z? - Nina Maharani; Allya Roosallyn Assyofa; Dede R Oktini; Ririn Sri Kuntorini (Research Synergy Foundation, 2026)
Retailers increasingly rely on private label products to strengthen store differentiation and improve margins. In contemporary retail environments characterized by digital marketing and omnichannel interactions, consumers often evaluate private label products based on their perceptions of the retail store and the value they derive from it. However, limited research has examined how store image shapes customer value and purchase intention among Generation Z, a digitally connected consumer segment. This study investigates the relationship between store image, customer value, and purchase intention for private label products among Generation Z consumers in modern retail settings. Data were collected through a survey of 175 respondents aged 16–27 who had purchased private label products from minimarkets, supermarkets, or hypermarkets in Bandung, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that store image significantly influences customer value, while its direct effect on purchase intention is not significant. Customer value, however, has a significant positive effect on purchase intention and fully mediates the relationship between store image and purchase intention. These findings highlight the importance of strengthening customer value perceptions through both in-store experiences and digital communication channels, particularly when targeting Generation Z consumers in omnichannel retail environments.